Making Sense of “Apportionment” in Patent Damages - Bailey, Elizabeth M.; Leonard, Gregory K.; Lopez, Mario A. (Science and Technology Law Review, 2011)
Unreasonably large damages awards in patent litigation have been an important force in motivating the movement for patent reform. “Apportionment” has found support as a solution to problem damages awards. Under apportionment, the portion of the overall value of the product that is “attributable” to the patented technology is identified. Then, reasonable royalty damages are calculated with reference to this apportioned value of the patented technology rather than the overall value of the product. While the problems that have motivated the apportionment movement are real and serious, apportionment makes sense as a solution only under the assumption that an economically invalid approach to calculating damages is being taken in the first place. A more sensible solution is to require litigants to take an economically valid approach to damages. In addition, when there are complementarities between assets, such that the combined use of two or more assets is worth more than their individual use, no unique way exists to apportion the overall value of the product among the assets (including the patented technology at issue), rendering apportionment infeasible in many cases. We consider these and other issues that surround apportionment.